HUBUNGAN POLA ASUH ORANG TUA TERHADAP MINDSET REMAJA AWAL DI KOTA BANDUNG - Cahyono, Maria Yuni Megarini; Zega, Trisa Genia; Hazna, Nadya (LPPM Institut Pendidikan Nusantara Global, 2023)
Recent research has found that the Growth Mindset increases one's motivation and achievement, both in academics, sports and work (Dweck, 2006). Individuals with a Growth Mindset will live themselves in the learning zone, and understand that their abilities can continue to develop in line with their efforts so they don't give up easily when facing challenges. Mindset is built through experiences and messages that individuals get when interacting with their environment. This study wanted to find out whether parenting style, which is a series of interaction patterns between children and parents (Santrock, 2014), has a relationship with mindset. Research on the relationship between parenting style and mindset of early adolescents will be examined in junior high school students in